2020
DOI: 10.1016/j.childyouth.2020.105317
|View full text |Cite
|
Sign up to set email alerts
|

Does early childhood education enhance parental school involvement in second grade?: Evidence from Midwest Child-Parent Center Program

Abstract: This paper examines the impact on parent involvement in second grade in the Midwest Child-Parent Centers (MCPC), a high-quality preschool-to-third-grade school reform model. A new focus of research on early childhood programs is understanding how early childhood learning gains can be sustained. Two-generation programs that provide diverse family services may be one approach. The MCPC expansion was implemented for a cohort of over 2000 Chicago and Saint Paul students beginning in preschool. Based on a compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(45 reference statements)
1
4
0
2
Order By: Relevance
“…Our results are consistent with research by Varshney et al (2020), which found that parent engagement has long been seen as a crucial component of programs that can enhance the success of early childhood interventions. By expanding learning time, enhancing student motivation and school engagement, and raising expectations for success and achievement, parental participation can improve children's outcomes (Varshney et al, 2020). Numerous literature reviews and study syntheses have reported on the benefits of parental participa- high expectations for their children's performance (Varshney et al, 2020).…”
Section: Lack Of Resources Influences Children's School Readinesssupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with research by Varshney et al (2020), which found that parent engagement has long been seen as a crucial component of programs that can enhance the success of early childhood interventions. By expanding learning time, enhancing student motivation and school engagement, and raising expectations for success and achievement, parental participation can improve children's outcomes (Varshney et al, 2020). Numerous literature reviews and study syntheses have reported on the benefits of parental participa- high expectations for their children's performance (Varshney et al, 2020).…”
Section: Lack Of Resources Influences Children's School Readinesssupporting
confidence: 92%
“…By expanding learning time, enhancing student motivation and school engagement, and raising expectations for success and achievement, parental participation can improve children's outcomes (Varshney et al, 2020). Numerous literature reviews and study syntheses have reported on the benefits of parental participa- high expectations for their children's performance (Varshney et al, 2020).…”
Section: Lack Of Resources Influences Children's School Readinessmentioning
confidence: 99%
“…Missing data were taken into account using a combined inverse-probability weighting and multiple imputation (IPW/MI) approach: IPW accounts for missing outcomes (i.e., lifestyle patterns) data whereas MI deals with missing data on contextual factors for these respondents (n = 978) [27]. As suggested by Seaman et al [27] and Varsh-ney et al [28], we conducted a comparative sensitivity analysis to assess the impact of missing data. More information is available in Additional Text S2 ("Handling missing data-detailed procedure").…”
Section: Handling Missing Datamentioning
confidence: 99%
“…Jonathan et al (2017) highlighted a negative attitude towards schooling, lack of strict discipline in school, and lack of parental monitoring as factors influencing the late coming of learners at schools. Parental involvement in their children's development has consistently been recognized as a key element that can promote the effectiveness of early childhood responsibility (Varshney et al, 2020). The nature of factors influencing late coming can be attributed to the exclusive complexity of social challenges facing male and female learners in society.…”
Section: Discussionmentioning
confidence: 99%